Response of Differently Structured Dental Polymer-Based Composites to Increasingly Aggressive Aging Conditions - Nicoleta Ilie (Nanomaterials)
Objective: It is hypothesized that the way nano- and micro-hybrid polymer-based composites are structured and cured impacts the way they respond to aging. Material and methods: A polymer–ceramic interpenetrating network composite (Vita Enamic/VE), an industrially polymerized (Brillinat CriosST/BC), and an in situ light-cured composite with discrete inorganic fillers (Admira Fusion5/AF5) were selected. Specimens (308) were either cut from CAD/CAM blocks (VE/BC) or condensed and cured in white polyoxymethylene molds (AF5) and subjected to four different aging conditions (n = 22): (a) 24 h storage in distilled water at 37 °C; (b) 24 h storage in distilled water at 37 °C followed by thermal cycling for 10,000 cycles 5/55 °C (TC); (c) TC followed by storage in a 75% ethanol–water solution; and (d) TC followed by a 3-week demineralization/remineralization cycling. CAD/CAM samples were also measured dry before the aging process. Three-point bending test, quantitative and qualitative fractography, instrumented indentation test (IIT), SEM, and reliability analyses were used. Uni- and multifactorial ANOVA, Tukey’s post hoc test, and Weibull analysis were performed for statistical analysis. Results: A significant (p < 0.001) and very strong effect of the parameter material was observed (ηP2 > 0.9). VE exhibited two to three times higher elastic moduli and hardness parameters compared to BC and AF5, which were comparable. Strength was highest in BC but was accompanied by high beam deformation. The effect of aging was comparatively smaller and was more evident in the IIT parameters than in the flexural strength or modulus. Reliability was high (m > 15) in VE and BC, regardless of aging protocol, while it was significantly reduced in AF5 following aging protocols b-d. Conclusions: TC was the method of artificial aging with a significant impact on the measured parameters, while demineralization/remineralization cycling had little or no impact. Clinical relevance: The degradation of composites occurred irrespective of the structuring and curing method and manifested in a low deterioration in the measured properties.